Information retrieval system (IRS) process on Hansard document / Suraya Saad - Saad, Suraya (2007)
Retrieving relevant speeches from Hansard document is one of the current problems in our Parliament. This research discusses about Information Retrieval process before we can search information on Hansard document easily and precisely. This research develops an algorithm which will enhance the current system. One of the IR process is to split the document into subdocument to ease searching relevant information. The algorithm will be developed to split the document into few subdocuments by using keywords. This research emphasizes that understanding how a data structure is used makes it clear how it is organized before we build an index to ease understanding of the construction algorithm which is usually more complex. Therefore with a proper process and use the right keywords the relevant information could be searched easily and precisely.